BIAYA PENGOBATAN PASIEN RAWAT INAP COVID-19 DI RUMAH SAKIT X TAHUN 2021 - Giusman, Reli; Nurwahyuni, Atik (Jurnal Ekonomi Kesehatan Indonesia, 2022)
The COVID-19 pandemic has caused various hospitals in the world to experience difficulties in providing services because the number of patients has soared in a short time. The widespread pandemic with high mortality in various parts of the country has resulted in high hospitalizations for patients due to COVID-19, so the cost of treatment has also increased. The purpose of this study was to analyze the cost of treating COVID-19 inpatients at Hospital X. The data used is secondary data derived from INACBG's data and medical records as many as 1,196 samples in the period August 2020 to April 2021. Statistical tests using the Mann Whitney Test, Kruskal Wallis Test and Spearman Test. The results showed that the average cost of treating COVID-19 inpatients at X Hospital was Rp.43,595,339.94. The difference between the real cost of treating COVID-19 inpatients with a positive claim fee of Rp. 48,622,313.07. The factors that influence the increase in the cost of treatment for COVID-19 inpatients at Hospital X are advanced age (> 60 years), male gender, higher education level, severity with moderate symptoms, having co-morbidities, length of stay, discharge status with recovery, the Doctor in Charge of the Patient (DPJP) is a lung specialist and collaboration of doctors > 3 doctors.